COVID-19 vaccine acceptance among pregnant women: a hospital-based cross-sectional study in Sudan - Saeed M. Omar; Osama S. Osman; Rehana Khalil; Osama Al-Wutayd; Ishag Adam (Frontiers Media S.A., 2023)
IntroductionPregnancy increases the risk of developing a severe illness due to COVID-19 infection. To the best of our knowledge, no previous study has been conducted on COVID-19 vaccine acceptance among pregnant women in Sudan. Hence, this study aimed to determine COVID-19 vaccination acceptance and its predictors among pregnant women.MethodsA cross-sectional study was conducted among 623 pregnant women attending Gadarif maternity hospital in eastern Sudan through a structured questionnaire. Data were obtained on sociodemographic characteristics, obstetric and health-related characteristics, COVID-19 infection, and vaccination-related information, as well as beliefs about and acceptance of COVID-19 vaccination.ResultsCOVID-19 vaccine acceptance among the pregnant women was 2.7%. The vaccine acceptance was higher if their husband's education was secondary school or higher [adjusted odds ratio [AOR] 4.30, 95% confidence interval (CI) 1.11-16.65, p = 0.035] and discussion of COVID-19 vaccine with the pregnant women by a health care professional in the hospital (AOR 5.46, 95% CI 1.94-15.35, p < 0.001). The most common reasons for resistance to the vaccine were concerns about the side effects of the vaccine for the mother and her baby.ConclusionAcceptance of the COVID-19 vaccination among the pregnant women was very low. Discussions with pregnant women and their husbands by health care professionals regarding the safety of COVID-19 vaccine for the mother and her baby are highly recommended.